A Systematic Review on History Teachers Practices towards Teaching Values Across the Curriculum - Mohamad, Norliza; Sihes, Ahmad Johari; Bohari, Normila Mohd; Suhaini, Mazlili (International Journal of Psychosocial Rehabilitation, 2020)
Values across the curriculum is an effort to integrate elements of values in the teaching and learning process in school subjects. Values occur in social sciences, and humanities course includes History education. The idea that history teachers should promote values in the curriculum is very significant and always debated even in science and technology epoch. History teachers have pivotal roles in teaching values, albeit they faced challenges. Several systematic reviews have been conducted on the History teachers’ practices of values. This study aims to explore the current research on History teachers’ practices towards teaching values across the curriculum. Preferred Reporting Items for Systematic Review and Meta-Analyses (PRISMA) as lead to direct this systematic review and 18 related studies have recognized and selected from databases Web of Science, Scopus, and Dimensions. Two research questions applied in this review to obtain themes within the data, and two significant themes arose, namely, teachers’ roles and teachers’ challenges. From the analysis of two main themes further presented a result of 10 sub-themes. In order to support History teachers and values across the History education implementation, necessary provisions need to be provided in such areas, teachers’ professional development and teacher education. Recommendations for future studies provided.